OUT RUNNING THE DEMONS : lives transformed through running - Hewitt, Phil; Karnazes, Dean, 1962- (London : BLOOMSBURY SPORT, 2019)
Running can take us to fantastic places. Just as importantly, it can also bring us back from terrible ones. For people in times of crisis, trauma and physical or mental illness, running is often the means by which they reconstruct fractured, fragmented identity - or indeed the means to a new identity. When normality collapses, running can put it back together again. In the very worst cases, it can actually create a new normality and offer us the chance to move on. 'Outrunning the Demons' is an in-depth exposition of just why running can so often be the answer to everything when we find ourselves in extremis. Written with insight and understanding - the author himself used running to rebuild his life after being viciously mugged - the book covers the themes of trauma, bereavement, depression & anxiety, addiction & alcoholism, violence/sexual abuse, long-term health conditions and eating disorders.
'An inspiring colection of stories about runners who have run through unimaginable adversity'.
Includes bibliographical references
Keywords: Hewitt, Phil; Runners (Sports) -- Biography; Running -- Psychological aspects; Biographies